The degree of acute descending control of spinal nociception in an area of primary hyperalgesia is dependent on the peripheral domain of afferent input - Drake, Robert A.R.; Hulse, Richard P.; Lumb, Bridget M.; Donaldson, Lucy F. (Wiley, 2014)
Descending controls of spinal nociceptive processing play a critical role in the development of inflammatory hyperalgesia. Acute peripheral nociceptor sensitization drives spinal sensitization and activates spino–supraspinal–spinal loops leading to descending inhibitory and facilitatory controls of spinal neuronal activity that further modify the extent and degree of the pain state. The afferent inputs from hairy and glabrous skin are distinct with respect to both the profile of primary afferent classes and the degree of their peripheral sensitization. It is not known whether these differences in afferent input differentially engage descending control systems to different extents or in different ways. Injection of complete Freund's adjuvant resulted in inflammation and swelling of hairy hind foot skin in rats, a transient thermal hyperalgesia lasting <2 h, and longlasting primary mechanical hyperalgesia (≥7 days). Much longer lasting thermal hyperalgesia was apparent in glabrous skin (1 h to >72 h). In hairy skin, transient hyperalgesia was associated with sensitization of withdrawal reflexes to thermal activation of either A- or C-nociceptors. The transience of the hyperalgesia was attributable to a rapidly engaged descending inhibitory noradrenergic mechanism, which affected withdrawal responses to both A- and C-nociceptor activation and this could be reversed by intrathecal administration of yohimbine (α-2-adrenoceptor antagonist). In glabrous skin, yohimbine had no effect on an equivalent thermal inflammatory hyperalgesia. We conclude that acute inflammation and peripheral nociceptor sensitization in hind foot hairy skin, but not glabrous skin, rapidly activates a descending inhibitory noradrenergic system. This may result from differences in the engagement of descending control systems following sensitization of different primary afferent classes that innervate glabrous and hairy skin.